2021
DOI: 10.1111/ijcp.14961
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pirfenidone and corticosteroid treatments at the COVID‐19 pneumonia with the guide of artificial intelligence supported thoracic computed tomography

Abstract: Aim We aimed to investigate the effect of short‐term pirfenidone treatment on prolonged COVID‐19 pneumonia. Method Hospital files of patients hospitalised with a diagnosis of critical COVID‐19 pneumonia from November 2020 to March 2021 were retrospectively reviewed. Chest computed tomography images taken both before treatment and 2 months after treatment, demographic characteristics and laboratory parameters of patients receiving pirfenidone + methylprednisolone (n = 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…As antifibrotic agents that interfere with processes of pulmonary fibrosis, nintedanib and pirfenidone might provide novel therapeutic approaches for minimizing post-COVID-19 fibrosis. 41,42 However, it is likely that nintedanib may increase the risk of bleeding when used together with anticoagulants. 43 In addition, both nintedanib and pirfenidone may lead to hepatotoxicity, which will further increase the likelihood of liver dysfunction often experienced by COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…As antifibrotic agents that interfere with processes of pulmonary fibrosis, nintedanib and pirfenidone might provide novel therapeutic approaches for minimizing post-COVID-19 fibrosis. 41,42 However, it is likely that nintedanib may increase the risk of bleeding when used together with anticoagulants. 43 In addition, both nintedanib and pirfenidone may lead to hepatotoxicity, which will further increase the likelihood of liver dysfunction often experienced by COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another encouraging trend in favor of pirfenidone was investigated in the Acat M. et al study that was conducted on hospitalized patients diagnosed with severe COVID-19 pneumonia, as it was discovered that pirfenidone can prevent the development of fibrosis. In addition, it can aid in dose reduction and/or non-use strategies for methylprednisolone therapy, which is associated with numerous adverse effects [ 36 ]. These observations were similar to the conclusions of a study that was carried out on patients with severe COVID-19 infection, and indicated that beginning pirfenidone medication as soon as possible is associated with a better treatment and survival outcome compared to corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Our patients were randomly separated into 2 groups. First group (25 cases) got pirfenidone in a dose of 267 mg tds at 1 st week, which was further raised in weekly dosage increments to a maximum of 2400 mg (13) , in addition to 20 mg/day corticosteroids (prednisolone). Second group (25 cases) received 20 mg /day corticosteroids (prednisolone) (14) .…”
Section: Table (2)mentioning
confidence: 99%
“…First group (25 patients) received pirfenidone beginning in the first week at a dose of 267 mg tds and progressively increasing to a maximum of 2400 mg in weekly dose additions after that (13) in combination with 20 mg/day corticosteroids (prednisolone).…”
mentioning
confidence: 99%